The Impact on Emergency Department Utilization and Patient Flows after Integrating with a General Practitioner Cooperative: An Observational Study. (2nd October 2013) - Thijssen, W. A. M. H.; Wijnen-van Houts, M.; Koetsenruijter, J.; Giesen, P.; Wensing, M.
Abstract : Introduction . A new model, an emergency care access point (ECAP) for after-hours emergency care, is emerging in The Netherlands. This study assessed the effect on emergency department (ED) utilization and patient flows. Methods . Routinely recorded clinical ED patient data, covering a six-year period, was collected. Segmented regression analysis was used to analyze after-hours changes over time. Results . 59.182 patients attended the ED before the start of the ECAP and 51.513 patients after, a decrease of 13%. Self-referred ED patients decreased 99.5% (OR 0.003; 95% CI 0.002–0.004). Referred patients increased by 213.4% and ED hospital admissions increased by 20.2%. A planned outpatient follow-up increased by 5.8% (OR 1.968 95% CI 1.870–2.071). The latter changed from fewer contacts to more contacts (OR 1.015 95% CI 1.013–1.017). Consultations at the regional genereral practitioner cooperative (GPC) increased by 26.0% (183.782 versus 232.246). Conclusion . ECAP implementation resulted in a decrease in ED utilization, a near absence of self-referring patients, and a higher probability of hospital admission and clinical follow-up. This suggests either an increase of ED patients with a higher acuity or a lower threshold of admitting referred patients compared to self-referred patients. Overall, increased collaboration with after-hours primary care and emergency care seemed to optimize ED utilization.